1997
DOI: 10.1515/text.1.1997.17.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Point of view and citation: Fourteen Chinese and English versions of the ‛same’ news story

Abstract: Fourteen versions ofthe same news story, a Xinhua release about Li Peng's meeting wifh George Bush, were selectedfor comparison front eleven Hong Kong newspapers and three from the Peoples Republic of China (PRC). Four are English language newspapers and the rest Chinese. Comparison of five features including switches in point of view, lamination, ambiguous quotation, bylining of a named reporter, andmention ofsetting in the lead revealed dijferences between English and Chinese texts in the structuring of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 5 publications
0
7
0
5
Order By: Relevance
“…The inverted pyramid is frequently referred to as the most common structure of English news reports in the press (as in Ferry 2006;Readership Institute 2004Scollon and Scollon 1997;Sternadori 2008;Thomson et al 2008). According to Readership Institute (2010), newspapers in the United States use the inverted pyramid style for 69 percent of all stories.…”
Section: Resultsmentioning
confidence: 99%
“…The inverted pyramid is frequently referred to as the most common structure of English news reports in the press (as in Ferry 2006;Readership Institute 2004Scollon and Scollon 1997;Sternadori 2008;Thomson et al 2008). According to Readership Institute (2010), newspapers in the United States use the inverted pyramid style for 69 percent of all stories.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth part, the conclusion, need not be decisive, but can indicate a doubt or ask a question. Hinds (1983) gives examples of Japanese newspaper editorials using this structure being translated sentence by sentence for the English version of the paper, and Scollon and Scollon (1997) show how this structure is used in both Chinese and English-language newspapers in Hong Kong, so it cannot be dependent on anything inherent to the linguistic or cognitive structures of a given language. Hinds (1987) describes this form of writing as "reader-responsible": it is the reader who has to make an effort and use inductive logic to provide the transitions and logical links between the sentences and paragraphs, unlike in "writerresponsible" cultures (such as the US and the UK) in which readers expect writers to use coherence devices and textual transitions to render explicit the connections between arguments.…”
Section: Contrastive Rhetoricmentioning
confidence: 99%
“…Although these are parts of a news text, they are not the article proper, on which we annotate rhetorical relations. 7 After a comparative study on the rhetorical structure of news published by some Hong Kong newspapers in both English and Chinese, Scollon and Scollon (1997) observed that "quotation is at best ambiguous in Chinese. No standard practice has been observed across newspapers in this set and even within a newspaper, it is not obvious which portions of the text are attributed to whom."…”
Section: Segmentationmentioning
confidence: 99%